DOI: 10.3990/1.9789036529587
|View full text |Cite
|
Sign up to set email alerts
|

Residual lifetime assessment of uPVC gas pipes

Abstract: Klis (www.loekvanderklis.com) and are used with permission. RESIDUAL LIFETIME ASSESSMENT OF UPVC GAS PIPES PROEFSCHRIFT SummaryThe Dutch gas distribution network consists of about 20% (22,500 km) of unplasticised poly(vinyl chloride) (uPVC) pipes, most of which have been installed from the mid-sixties up to the mid-seventies of the previous century and have been in service ever since. In the next decade the specified service lifetime of 50 years will be reached for these pipes. Replacing the uPVC gas pipes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 159 publications
0
5
0
Order By: Relevance
“…Previously it was shown that hardness measurement results correlate with the yield strength observed in tensile testing [26]. Therefore the non-collinear wave mixing results were verified partially employing micro-indentation experiments.…”
Section: Measurement Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Previously it was shown that hardness measurement results correlate with the yield strength observed in tensile testing [26]. Therefore the non-collinear wave mixing results were verified partially employing micro-indentation experiments.…”
Section: Measurement Resultsmentioning
confidence: 77%
“…Physical ageing was, however, investigated with other measurement techniques for a wide range of glassy polymers. In particular, physical ageing of PVC was investigated by means of: measurement of the creep compliance [12][13][14][15][16][17]; measurement of the heat distortion temperature [18]; differential scanning calorimetry [19][20][21][22]; dynamic mechanical spectroscopy (dynamic mechanical analysis) [23]; tensile test measurements [2,24,25]; micro-indentation tests [26].…”
Section: Introductionmentioning
confidence: 99%
“…This can be described in three stages (Butters, 1982): the stage III-PVC particle ($100-150 lm), the stage II-primary particle ($0.1-2 lm) and the stage I particle ($10 nm). The conversion of the material to a homogeneous product requires that the boundaries of the primary particles disappear and a new continuous entanglement network is developed (Visser, 2009). This procedure is known as the gelation process and its quality is expressed by the gelation level.…”
Section: Productionmentioning
confidence: 99%
“…A temperature of >250 C is needed for this purpose (Guerrero & Keller, 1981), much higher than the degradation temperature of PVC which is $205 C (Wypych, 2015). Due to this fact, thermal energy is complemented with mechanical energy (high shear stresses) by the use of twin rotating screws, so as to accelerate this process without extensive exposure of the material to high temperatures (Visser, 2009). Subsequently, the molten material is introduced in a die so that the final pipe is shaped and cooled.…”
Section: Productionmentioning
confidence: 99%
“…KIWA uses stress-strain tests executed in their laboratory facilities in Apeldoorn for predicting service life of network components, mainly being PVC, PE and grey cast iron pipes. Roy Visser [106] uses a hybrid technology: technically, a pipe is damaged using a needle (micro indenture), but since the indenture is very shallow and small (micro scale) the pipe can still be in operation.…”
Section: Ndt Quality Inspectionmentioning
confidence: 99%